PENGEMBANGAN TARI PODANG PERISAI DARI TRADISI MENJADI MODERN DI KUANTAN SINGINGI RIAU - Ali Sukri (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
This paper is the result of research on the development of Dance Podang Perisai from tradition to be modern both textually and contextually. Textually Dance Podang Perisai is related to dance composition including motion, dancers, musical, accompaniment, costum, makeup and dloor pattern, created by traditional artists who have not had any knowledge about choreography so Dance Podang Perisai is very simple according to requirement at that time. Dance Podang Perisai has seven different motions of starting motion, sosor, paliang, rantak sabolah, rantak duo bolah, kuak ilalang and lantiang pauah. From a contextual point of view, Dance Podang Perisai is analyzed about the values of past struggles that must be maintained so as not to simply disappear with the presence of increasingly sophisticated technology that makes the tradition’s values more neglected. Development of research based Dance Podang Perisai with method R & D (Research and Development). The research begins in the Dance of Podang Perisai tradition and is developed into a modern dance.